Priming Mesenchymal Stem Cells with Lipopolysaccharide Boosts the Immunomodulatory and Regenerative Activity of Secreted Extracellular Vesicles - Aina Areny-Balagueró; Marta Camprubí-Rimblas; Elena Campaña-Duel; Anna Solé-Porta; Adrián Ceccato; Anna Roig; John G. Laffey; Daniel Closa; Antonio Artigas (MDPI AG, 2024)
Background: Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been proposed as an alternative to live-cell administration for Acute Respiratory Distress Syndrome (ARDS). MSC-EVs can be chiefly influenced by the environment to which the MSCs are exposed. Here, lipopolysaccharide (LPS) priming of MSCs was used as a strategy to boost the natural therapeutic potential of the EVs in acute lung injury (ALI). Methods: The regenerative and immunemodulatory effect of LPS-primed MSC-EVs (LPS-EVs) and non-primed MSC-EVs (C-EVs) were evaluated in vitro on alveolar epithelial cells and macrophage-like THP-1 cells. In vivo, ALI was induced in adult male rats by the intrapulmonary instillation of HCl and LPS. Rats (n = 8 to 22/group) were randomized to receive a single bolus (1 × 108 particles) of LPS-EVs, C-EVs, or saline. Lung injury severity was assessed at 72 h in lung tissue and bronchoalveolar lavage. Results: In vitro, LPS-EVs improved wound regeneration and attenuated the inflammatory response triggered by the P. aeruginosa infection, enhancing the M2 macrophage phenotype. In in vivo studies, LPS-EVs, but not C-EVs, significantly decreased the neutrophilic infiltration and myeloperoxidase (MPO) activity in lung tissue. Alveolar macrophages from LPS-EVs-treated animals exhibited a reduced expression of CXCL-1, a key neutrophil chemoattractant. However, both C-EVs and LPS-EVs reduced alveolar epithelial and endothelial permeability, mitigating lung damage. Conclusions: EVs from LPS-primed MSCs resulted in a better resolution of ALI, achieving a greater balance in neutrophil infiltration and activation, while avoiding the complete disruption of the alveolar barrier. This opens new avenues, paving the way for the clinical implementation of cell-based therapies.